THE EFFECT OF JEOPARDY GAME TOWARD STUDENTS’ VOCABULARY MASTERY - Marsika Sepyanda (Universitas Mahaputra Muhammad Yamin, 2021)
Vocabulary is one of the language aspects that should be mastered by the students in language learning. It has a main role for the students in understanding and applying the four basic skills in language learning. Most of the teachers do not pay attention to the media that they use in gaining students’ vocabulary mastery. This study aimed to find out whether the use of Jeopardy Game affected the students’ vocabulary mastery or not. This study conducted a quasi-experimental design. The population of this study was comprised of 186 students of the second grade of SMAN 1 Bukit Sundi that divided into 6 classes. The instrument of this study was a vocabulary test. The experiment class was taught by using Jeopardy Game, while the control class by using Guessing Game. In conclusion, there were significant differences between students who were taught by using Jeopardy Game and Guessing Game on Second Grade of SMAN 1 Bukit Sundi in 2020/2021 Academic Year